« Ici, pas de politique » - Alfredo Mignini (Cahiers d’histoire.)
Italians are the largest immigrant community within the Swiss melting pot during the “Golden age” of 20th century. Their migrant experience was however far from being free of conflicts. Political engagement and participation were seen with suspicion, due first to a strong anticommunist posture during the Cold war and then to a growing wave of xenophobic feelings. Current literature points out the network of clubs and societies as a substitute to traditional political engagement. This article deals with Otello Palmieri’s atypical life trajectory: after taking part to the Resistance war as a member of the Italian communist party and reaching Prague as a political refugee in 1949-53, as soon as he arrived in Switzerland he dismissed all political activity, although his interest in Italian political affairs remained acute. Hence, this case study highlights an original way to articulate the dialectic engagement/disengagement and allows to shed new lights on biography linearity.